Pengaruh Pendidikan Kesehatan Terhadap Perilaku Perawatan Gigi Anak Sekolah Dasar - Delima Br Sihombing; Regista Trigantara; Andi Surya Kurniawan (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: The purpose of the study was to analyze the impact of dental health education on the dental care behavior of fifth-grade students at Anak Saleh Elementary School, Malang City. Methods: The research used in this research is Quasi-Experimental Design, with a Pretest Posttest Nonequivalent Control Group Design. The research sample consisted of 54 respondents from fifth-grade elementary school students. The data analysis technique uses the paired sample t-test. Results: The research results showed that the majority of respondents had dental care behavior in the adequate category, 29 respondents or 53.7% before dental health education. The majority of respondents had dental care behavior in the good category, with 34 respondents or 63.0% after dental health education. The influence of education about dental health on dental care behavior in fifth-grade elementary school children at Saleh Children's Elementary School, Malang City with a Sig value. (2-tailed) of 0.000 < 0.05. Discussion: Dental health education in elementary schools is made a routine agenda every year.